Ideal Factor Analysis of Implementation Management Due to Waste Material of Building Construction Materials on Contractor Projects In Indonesia - James Thoengsal; Miswar Tumpu (Eduvest - Journal of Universal Studies, 2022)
The implementation of building construction projects cannot be separated from the problem of wasting costs, which is one of the contributing factors due to the emergence of residual materials during the construction process. The purpose of this study is to identify and analyze the ideal indicators in the application of construction material waste management in an effort to reduce the impact of cost inefficiency due to the of waste material so far, which in this study is viewed from the point of view of the parties involved in the building project. The results obtained from this study are that the ideal factor for implementing the ideal construction material waste management. Where at the planning/design stage, the most priority variable category is the Selection of Low Waste Materials, then at the procurement stage, namely the Estimation and Ordering of Material Volume and at the construction stage, namely the category Management Commitment category variables. The direction of research development is in the form of developing the concept of an ideal building construction material waste management model that can be applied by the construction operator, in this case addressed to the contractor, planning consultant and material supplier in an effort to reduce the impact of inefficiency in material costs during the construction process in Indonesia.